1996
DOI: 10.1093/oxfordjournals.jjco.a023218
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor Extent and Location on Treatment Outcome in Patients with Stage III Non-small Cell Lung Cancer Treated with Radiation Therapy

Abstract: The results of treatment of 141 patients with stage III non-small cell lung cancer (NSCLC) who received definitive radiation therapy at Gunma University Hospital between 1976 and 1989 were retrospectively analyzed. Radiation was given with standard fractionation for a planned prophylactic dose of 40 Gy over 4 weeks and a definitive dose of 60 Gy over 6 weeks or more. The two- and five-year survival rates were 27% and 12% for stage IIIA, and 18% and 8% for stage IIIB, respectively (P = 0.052). By univariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Twenty‐five studies were selected for the full‐text review. Finally, 10 retrospectively designed studies were included as relevant to assess our hypothesis . Studies excluded from full‐text review and reasons for exclusion are described in the Supplement data 3 in Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies were selected for the full‐text review. Finally, 10 retrospectively designed studies were included as relevant to assess our hypothesis . Studies excluded from full‐text review and reasons for exclusion are described in the Supplement data 3 in Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the contrary of Inoue, Ichinose et al (13) found that the survival was better in left lower lobe tumors in the patients with N2-positive stage 3A tumors. In the study by Hayakawa et al (14) conducted on the patients who received definitive radiotherapy without being operated, the survival of the upper lobe tumors was observed to be better than the lower lobe tumors. In our study, no statistically significant difference was found in both of relapse-free survival and overall survival in stage 3A patients in terms of tumor localization.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 Involvement of supraclavicular lymph nodes also increases the risk of eventual failure. 24 Outcomes with radiotherapy are somewhat better for squamous cell carcinoma than for other tumor types.…”
Section: Radiotherapy For Inoperable Stage III Non-small Cell Lung Camentioning
confidence: 99%
“…24 Outcomes with radiotherapy are somewhat better for squamous cell carcinoma than for other tumor types. 27 The location of the primary tumor also may be relevant. 28 If a patient has a peripheral lower lobe primary tumor and nodal involvement, then the size of the radiotherapy field and the amount of lung destroyed by the radiotherapy will be relatively large, whereas the size of the radiotherapy field is much smaller and the amount of radiation damage to lung is much less if the patient has a centrally placed upper lobe tumor, and the probability of survival is higher with inoperable upper lobe tumors than with inoperable tumors in other locations.…”
Section: Radiotherapy For Inoperable Stage III Non-small Cell Lung Camentioning
confidence: 99%
See 1 more Smart Citation